THE ROLE OF DIGITALIZATION IN PROJECT BASED CURRICULUM - Andi Irma Sarjani (International Journal of Teaching and Learning, 2024)
Digitalization in the education curriculum is an effort to support the online learning process without reducing the essence of delivering the material. Online learning is flexible to use, anywhere you can learn without having to meet the teacher. With this, schools can provide a platform that can be used to access student learning every day. School digitalization aims to increase the effectiveness, efficiency and overall quality of education following increasingly advanced technological developments. By implementing digital technology in schools, the learning process can become more interactive, interesting and easily accessible to all students equally. In the educational curriculum there is a project-based learning method which is one of the independent learning programs where learning is carried out collaboratively so that one class is divided into several groups. In project-based learning, students carry out investigations through daily experiences in solving problems from a question asked. It is hoped that from this process students will understand the benefits of learning which will be useful for their future life. The research methodology employed in this article is literature study, which is the process of conducting research using books, relevant journal collections, reports of research findings from earlier research, or other types of literature (library). The definition of digitalization in the context of education curricula, project-based learning, and its significance in the age of digitalization are all covered in this study.